From the Hippocratic Oath to modern deontological codes: continuity or overcoming? - Altamura, Bruno M. (Medicina e Morale, 1984)
Even if the Hippocratic Oath in its enlightened synthesis encapsulates the essence of the great master's deontological teachings, there is no doubt that a more complete picture of Hippocratic ethics can be gleaned from the contents of the entire Corpus Hippocraticum, and it matters little if the various writings contained therein are not all attributable to him, but are in fact the work of various authors who lived between the 5th and 2nd centuries BC.